Controlled Planar Alignment of Discotic Liquid Crystals in Microchannels Made Using SU8 Photoresist. (25th June 2013) - Cattle, James; Bao, Peng; Bramble, Jonathan P.; Bushby, Richard J.; Evans, Stephen D.; Lydon, John E.; Tate, Daniel J.
Abstract A range of triphenylene and phthalocyanine‐based discotic liquid crystals (DLCs) can be aligned within micrometer‐scale channels formed from SU8 patterned on silicon or glass surfaces. The channels can be filled with the DLC in its isotropic phase using capillary action. Alignment occurs spontaneously as the sample is slowly cooled into the Colh phase. Whilst all of these DLCs align with the columns perpendicular to the surface when they are 'sandwiched' between glass slides, in these channels, the DLC aligns with the column director parallel to the surface. It is also constrained to lie across the channels. The same alignment occurs when these DLCs are confined between SU8‐topped interdigitated gold electrodes where it gives the optimum orientation for electrode‐to‐electrode conduction. The quality of the alignment depends on the particular liquid crystal used and on the width of the channel. For the Colr phase of octaoctylphthalocyanine there is additional epitaxial control over the orientation of the lattice such that the a/c face of the lattice is parallel to the surface. This is an important prerequisite for creating a bistable display device that switches by virtue of changing the direction of the tilt of the discs.